Sistem Pengupahan Buruh Tani Dalam Perspektif Hukum Islam (Studi Desa Yosorati Kecamatan Sumber Baru Kabupaten Jember) - Hannan, Fais Faizul; Kholifah, Nur; Azakia, Kiki (LAN TABUR : Jurnal Ekonomi Syariah, 2023)
One form of Mu'amalah that occurs is cooperation between humans, on the one hand, being service/power providers, who are called laborers, and humans, on the other hand, providing jobs, who are called employers, to carry out a production activity, provided that the workers will receive compensation. in the form of compensation. In this case, Islam responds to this fact by offering a concept, one of which is Ijarah regarding the leasing of human labor or an employment agreement between a worker and an entrepreneur called Ijarah 'Al-A'ma. The method in this study uses a descriptive qualitative method. While the approach in this research is a qualitative approach and this type of research is descriptive research. In this case, the circumstances, conditions, situations, events, or life activities that exist in society are the most important elements in the studies conducted. The Farmer Wages System implemented in Yosorati Village, Sumber Baru District, Jember Regency pays close attention to the principles of justice as taught by Islam so as to be able to provide welfare for workers and be able to meet the needs of their families. In Islam, wages for work should at least be able to meet basic needs, food, clothing and boards with a measure of the standard of living of the community environment.